Nutritional Status Does Not Correlate with Stump Complications in Two-stage Lower Extremity Amputations. Issue 10 (October 2015) - Keeley, Jessica; Kaji, Amy; Kim, Dennis; Plurad, David; Putnam, Brant; Neville, Angela
Unsalvageable foot infections require a two-staged amputation: an initial guillotine below-knee amputation (BKA) followed by formalization. No literature exists regarding the optimal timing to formalization, and the role of nutrition on outcomes remains unclear. This study was conducted to evaluate whether timing to formalization or nutritional markers correlate with stump complications. A retrospective review of all guillotine BKAs done at our county-funded, academic medical center between 2008 and 2013 was performed. Comorbidities, albumin, prealbumin, glycated hemoglobin, days to formalization, and postoperative complications were recorded. Primary outcome was surgical site infection or need for reoperation of the formalized stump within 30 days. One hundred and twenty-eight guillotine BKAs and subsequent formalizations were performed. Twenty-two (17.2%) patients developed surgical site infections and six (4.9%) required reoperation. Patients formalized within 14 days were as likely to develop stump complications as those formalized later (odds ratio 0.7, 0.3–1.8, P = 0.5). When comparing patients who developed stump complications to those who did not, there was no difference in preoperative albumin (2.6 ± 0.7 vs 2.4 ± 0.7, P = 0.3), prealbumin, (14.4 ± 6.2 vs 15.2 ± 5.5, P = 0.5), or glycated hemoglobin (8.8 ± 2.9 vs 9.0 ± 2.5, P = 0.7). Neither timing of formalization nor nutritional parameters predicted wound complications.